2018
DOI: 10.1080/13621718.2018.1430114
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mechanical properties of a welded CoCrFeMnNi high-entropy alloy

Abstract: The response of the CoCrFeMnNi high-entropy alloy to weld thermal cycles was investigated to determine its applicability as an engineering structural material. Two processes were used: high-energy-density, low-heat-input electron beam (EB) welding and low-energy-density, highheat-input gas tungsten arc (GTA) welding. Weldability was determined through comprehensive microstructural and mechanical property characterisation of the welds. The welds did not develop solidification cracking or heat-affected zone crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 64 publications
3
49
0
Order By: Relevance
“…The obtained results demonstrate for the first time the possibility to produce sound butt joints of the Ti 1.89 NbCrV 0.56 RHEA by LBW, which is an important step toward potential practical applications of this new class of metallic alloys. However, the present study also emphasized the importance of LBW process parameters (particularly pre-heating temperature) to obtain good results, which is quite different from the transition metals HEAs [27][28][29][30][31][32]44,45]. Given the wide range of the available RHEAs compositions [7], specific attention should be paid to select proper welding conditions for each individual alloy.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The obtained results demonstrate for the first time the possibility to produce sound butt joints of the Ti 1.89 NbCrV 0.56 RHEA by LBW, which is an important step toward potential practical applications of this new class of metallic alloys. However, the present study also emphasized the importance of LBW process parameters (particularly pre-heating temperature) to obtain good results, which is quite different from the transition metals HEAs [27][28][29][30][31][32]44,45]. Given the wide range of the available RHEAs compositions [7], specific attention should be paid to select proper welding conditions for each individual alloy.…”
Section: Resultsmentioning
confidence: 84%
“…Weldability is another crucial technological property of the structural materials, since welding is one of the most reliable and efficient ways of joining different parts together. A few studies on welding of HEAs were reported recently [27][28][29][30][31][32]. The efficiency of using arc welding [28], laser beam welding (LBW) [31], electron beam welding [27,28], and friction stir welding [29,30,32] was shown to obtain sound joints in HEAs with reasonable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] have already been reported on fusion-based welding of HEAs. To date, these works focus mainly on laser-based techniques, although some information is also available on Electron Beam and Gas Tungsten Arc Welding (GTAW) techniques.…”
Section: Fusion-based Welding Of Heasmentioning
confidence: 99%
“…Concerning other fusion-based welding techniques, Wu et al [60,61] investigated Electron Beam Welding and Gas Tungsten Arc Welding (GTAW) on a CoCrFeMnNi HEA. For this purpose, ingots were produced via arc-melting and then thermomechanically processed to achieve a homogeneous equiaxed microstructure.…”
Section: Cocrfenimn Hea Systemmentioning
confidence: 99%
“…There are many studies on welding HEAs [35][36][37]. Good mechanical properties have been achieved in previous studies [38][39][40]. However, very limited researches are focused on brazing HEAs [41].…”
Section: Introductionmentioning
confidence: 99%